Relationship Between Plasma 8‐OH‐Deoxyguanosine and Cardiovascular Disease and Survival in Type 2 Diabetes Mellitus: Results From the ADVANCE Trial. Issue 13 (3rd July 2018) - Thomas, Merlin C.; Woodward, Mark; Li, Qiang; Pickering, Raelene; Tikellis, Christos; Poulter, Neil; Cooper, Mark E.; Marre, Michel; Zoungas, Sophia; Chalmers, John; ,
Abstract : Background: 8‐Oxo‐2′‐deoxyguanosine (8‐oxo‐2′‐dG) is a biomarker of oxidative DNA damage that is associated with cardiovascular disease and premature mortality in the general population. Although oxidative stress has a proven role in cardiovascular complications in diabetes mellitus, evidence for a relationship between plasma 8‐oxo‐2′‐dG and major cardiovascular outcomes in diabetes mellitus is weak. Methods and Results: A case‐cohort study was performed in 3766 participants with prevalent diabetes mellitus in the ADVANCE (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation) trial (ClinicalTrials.gov number NCT00145925). The hazard ratios for mortality and major acute cardiovascular events were derived using Cox regression models. During a median of 5 years of follow‐up, 695 (18.4%) participants in this enriched cohort died (including 354 deaths from cardiovascular disease). Individuals with higher levels of 8‐oxo‐2′‐dG were more likely to die. After adjusting for cardiovascular disease risk factors, the hazard ratio for a 1‐SD increase in plasma 8‐oxo‐2′‐dG was 1.10 (95% confidence interval, 1.01–1.20; P =0.03). This was driven by an independent association between plasma 8‐oxo‐2′‐dG and cardiovascular death (hazard ratio, 1.23; 95% confidence interval, 1.10–1.37 [ P <0.001]). By contrast, no association was seen between 8‐oxo‐2′‐dG and noncardiovascular disease death (of which cancer was the major single cause). 8‐Oxo‐2′‐dG was also not significantly associated with either nonfatal myocardial infarction or nonfatal stroke. Conclusions: In adults with type 2 diabetes mellitus, increased levels of 8‐oxo‐2′‐dG are independently associated with all‐cause mortality and cardiovascular mortality in adults with longstanding type 2 diabetes mellitus who participated in the ADVANCE trial, consistent with the role of oxidative damage in the development and progression of cardiovascular decompensation in diabetes mellitus. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00145925.